The Relational Character of Canadian Nation‐Building Infrastructure in the 21 st Century - Alaz Munzur; Katharina Koch (Canadian Public Administration, 2026)
Abstract Infrastructure development is central to Canada's nation‐building process. This article argues that the federal government has recalibrated its nation‐building mandate from unilateral state command to relational orchestration. Through thematic analysis of thirty‐eight policy documents related to three federal infrastructure plans (2007–2016), we show that “nation‐building infrastructure” has evolved from large‐scale projects to an umbrella term encompassing community‐focused initiatives and both hard and soft infrastructure. The federal government now channels investment through partnerships with provinces, municipalities, territories, private capital, and Indigenous rights holders. This shift represents not federal withdrawal but a strategic repositioning of federal power through coordinated, multi‐actor arrangements.